2016
DOI: 10.1155/2016/8314561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tactile Sensitivity on Structural Variability of Digit Forces during Stable Precision Grip

Abstract: This study investigated the effects of fingertip tactile sensitivity on the structural variability of thumb and index finger forces during stable precision grip. Thirty right-handed healthy subjects participated in the experiment. Transient perturbation of tactile afferents was achieved by wrapping up the distal pads of the thumb or index finger with transparent polyethylene films. The time-dependent structure of each digit force and the variability of interdigit force correlation were examined by detrended fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Considering the precision grip is a sensorimotor process, the motor systems are under both feedforward and feedback controls. The feedforward mechanism allows individuals to program appropriate motor commands prior to grasping according to previous experiences of the object properties; whereas the feedback mechanism adjusts neuromuscular activations according to real-time sensory information 27 , 34 , 43 . By examining the grip force performance in process of holding to lifting an object, Chiu et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the precision grip is a sensorimotor process, the motor systems are under both feedforward and feedback controls. The feedforward mechanism allows individuals to program appropriate motor commands prior to grasping according to previous experiences of the object properties; whereas the feedback mechanism adjusts neuromuscular activations according to real-time sensory information 27 , 34 , 43 . By examining the grip force performance in process of holding to lifting an object, Chiu et al .…”
Section: Discussionmentioning
confidence: 99%
“…By this set-up the thumb and index finger need to comply with mechanical or task constraints such as producing zero residual forces and moments; guaranteeing enough load force to counterbalance the weight of the handle; avoiding handle tilt from unbalanced forces across the digits, and accommodate to the load perturbations, etc. To fulfill all these constraints the motor system needs to produce well-coordinated digit forces 34 , 56 . The DM-related patterns observed in the dynamical muscle coordination were associated with the inter-digit force coordination during precision grip of a freely moveable apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, IFA operates as a self-invoking trigger that worsens the motor performance by focusing on the proprioceptive information from the finger [ 43 ]. Both these submodalities of the haptic sense are involved in motor planning and control of the effector [ 28 ], but the exteroceptive source (in our case the tactile sensation derived from the keys) seems to be the more relevant for a fine motor control of the fingers [ 44 46 ]. Furthermore, no differences were found between the motor performance obtained in IFA and control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This excessive force is a response to poor tactile sensitivity (Cole, 1991). For this study, the pulp pinch was selected as the type of pinch technique to be experimented on according to supports from previous studies (Cole, 1991;Li, Wei, Yue et al, 2016a, 2016b. It was also suggested that the pulp pinch is one of the more commonly used dual finger pinching techniques with regard to maximum strength applications for small objects (Nilsen et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%